Flexural behaviour of strengthened damaged steel beams using carbon fibre-reinforced polymer sheets - Wenyu Hou; Lianguang Wang; Di Shi (Scientific Reports, 2022)
Abstract This paper presents the test and finite element analysis results of a study on the flexural behaviour of damaged steel beams strengthened with carbon fibre-reinforced polymer (CFRP) sheets. The test results showed that the yield load, ultimate load and elastic stiffness of the steel beams with 100% loss of tension flange were 68.3%, 73.8% and 13.5% greater than the yield load, ultimate load and elastic stiffness of the steel beam with 28% loss of the web after static loading. The yield load and elastic stiffness of the steel beam after overloading were 8.7% and 24.5% greater than the yield load and elastic stiffness of the steel beam without overloading. The damage level had a significant effect on the yield load, ultimate bearing capacity and elastic stiffness of the steel beams regardless of whether the steel beams were under static loading or overloading. The damaged steel beam could be repaired by CFRP sheets, the increased layers of CFRP sheets could improve the yield load, ultimate bearing capacity and elastic stiffness of the steel beams, and the strains of CFRP sheets would decrease because of overloading. The numerical analysis results showed that compared with the steel beam without overloading, the deflection and strains of the steel beam after overloading were much smaller. The yield load and the elastic stiffness increased with the increment of the overloading amplitude, and the increment of overloading number could reduce the yield load and elastic stiffness. All the yield loads of the steel beams after overloading were greater than the yield loads of the steel beams without overloading, but the ultimate bearing capacities were smaller.